STRATEGI KEBUDAYAAN SYEIKH ZAINUDIN RE-FORMULASI PENDIDIKAN ISLAM DI LOMBOK - Muharir (eJurnal Al Musthafa, 2023)
Al Mujahidin Islamic boarding school as a laboratory for testing semi-classical learning model. As a center of education. TGKH. Muhammad Zainuddin Abdul Majid reformed on two things. First : renewal of learning methods [integration of halaqoh and classical system]. Second, when the sasak people made the Malay Arabic book the main reference. Al Mujahidin Islamic boarding school in all learning activities add references to Arabic books, this is done to make easier the students to understand primary sources of islam including Alqurán and Al-Hadits. In conducting preaching and developing Islamic education in Lombok, TGKH. Muhammad Zainuddin Abdul Majid was using a cultural approach, at least there are two aspects of culture that are used as a foothold. First : compose sasak songs in dakwah approach. For example “Pacu Gama”, “ ya fata Sasak”, that songs hummed an invitation to be religions the lyric is inak amak ku semeton jari ku pada ndek narak ita gen kekel lek dunia… dakak ta sugi dakak ta bangsa mulia ndek narak guna mun ndek narak agama …..and many others. By this way. TGKH. M. Zainuddin Abdul Majid shows how to convey religious message within the frame work “ bi lisani qaumi”. Second : established an Islamic organization as a local organization which was founded in 1953. The NW establishment shows independence TGKH. M. Zainuddin Abdul Majid he gave an example that the sasak people should be able to stand on their own, able to manage their organization. Even though we understand that the sasak ethnic has a small population and is far from of power.